Konflik Internal dan Konflik Eksternal Tokoh dalam Novel Tenggelamnya Kapal Van Der Wijck Karya Buya Hamka - Hawiah Djumadin; Rosa Dalima Bunga (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2020)
The formulation of the problem in this study is how the internal and external conflicts of the main character in Buya Hamka's novel Tenggelamnya Kapal Van Der Wick. The purpose of this research is to identify and describe the internal and external conflicts of the main character in Buya Hamka's novel Tenggelamnya Kapal Van Der Wick. Qualitative descriptive approach. The data used in this study are in the form of words, phrases and sentences. The data source is the novel Tenggelamnya Kapal Van Der Wijck by Buya Hamka, the 22nd print, with a total of 228 pages. Data collection techniques are reading notes. Data analysis techniques, namely; (1) data reduction, (2) data codification, (3) data classification, (4) data description, (5) data interpretation, (6) data verification. The theory used is the theory of psychoanalytic development. The results showed internal conflicts, namely: a) uncertainty, b) feelings of love, c) feelings of sadness, d) feelings of fear, e) feelings of sadness. External conflicts, namely a) conflicts between Hayati and other characters, b) relationships that are not sanctioned, c) feelings of depression over loss, d) quarrels between Hayati and Khadijah, e) Zainudin 's disappointment because his love was betrayed by Hayati, f) Hayati experienced the inner stress of following your parents' choices.